Developing Building Management System Framework using Web-based-GIS and BIM Integration - Brigitta Petra Kartika Narindri; Arief Setiawan Budi Nugroho; Akhmad Aminullah (Civil Engineering Dimension, 2022)
Building Information Modeling (BIM) and Geographic Information systems (GIS) are two digital system innovations advantageously applied in the Architecture, Engineering, Construction, and Operations (AECO) sectors. GIS and BIM integration development is indispensable in building and infrastructure management. This integration promises several benefits for the operational phase of buildings and infrastructures. However, it faces challenges in data transformation and collaboration. This study proposes a framework and model for a web-based building management platform. The framework is developed by transforming BIM data into the GIS environment using the latest technology from ArcGIS. It allows data-sharing and collaboration among stakeholders, help build management, and is valuable for decision-making. The stakeholders, who do not need a BIM-GIS expert, could virtually see the report and updates of this building model every time.